1989
DOI: 10.1111/j.1939-0025.1989.tb01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a family support program on mothers' social support and parenting stress.

Abstract: The study examined two components of a family support program, a mothers' self‐help discussion group and a parent education group, to determine their effects on social support and parenting stress. Findings suggest that, after three months of program participation, mothers in both groups felt less social isolation and parenting stress than did mothers in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
2
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 16 publications
0
53
2
1
Order By: Relevance
“…Some previous investigations have found that higher social support is associated with lower parenting stress ( McConnell, Breikreuz, & Savage, 2010 ) and at least one intervention directed at improving mothers' support was shown to decrease parenting stress ( Telleen, Herzog, & Kilbane, 1989 ). As Belsky (1984 ) has suggested, social support may reduce parenting stress directly if other individuals help with childcare tasks or commend the parent's handling of childcare issues.…”
Section: The Psychosocial Context Of Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous investigations have found that higher social support is associated with lower parenting stress ( McConnell, Breikreuz, & Savage, 2010 ) and at least one intervention directed at improving mothers' support was shown to decrease parenting stress ( Telleen, Herzog, & Kilbane, 1989 ). As Belsky (1984 ) has suggested, social support may reduce parenting stress directly if other individuals help with childcare tasks or commend the parent's handling of childcare issues.…”
Section: The Psychosocial Context Of Parentingmentioning
confidence: 99%
“…Romantic partners and other close confi dants can do much to mitigate the eff ects of adversity by responding to mothers' emotional needs. Support-based interventions may also be appropriate given that parenting support groups ( Telleen, et al, 1989 ) and home-visiting programs ( Armstrong, Fraser, Dadds, & Morris, 1999 ) have been shown to reduce parenting stress.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Social support exerts a broad positive influence on personal health, [23][24][25] maternal-child relations, child psychosocial functioning and family functioning. [26][27][28][29][30] Maternal education about child development can lead to improved child competence, academic test performance and intelligence quotients. [31][32][33][34] Parent management training, both group based and individually tailored, has been shown to have a positive effect on parenting and on children's emotional and behavioural adjustment.…”
Section: 22mentioning
confidence: 99%
“…The Resource Size Scale developed by Telleen lists 11 categories of people from the family and 8 from the community system in each of seven functional areas (Telleen et al, 1989). A support person is one perceived by the pregnant student as being available for support during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents view family members, especially their mothers, as their most important sources of support (Zimet, Powell, Farley, Werkman, & Berkoff, 1990). Living with one or both parents was found to increase the length of participation in parenting programs (Telleen, Herzog, & Kilbane, 1989). Siblings and friends provided task assistance and emotional support.…”
mentioning
confidence: 99%